2007
DOI: 10.1063/1.2786573
|View full text |Cite
|
Sign up to set email alerts
|

Energy level alignment of electrically doped hole transport layers with transparent and conductive indium tin oxide and polymer anodes

Abstract: Using ultraviolet photoemission spectroscopy, we investigated the energy level alignment at the interfaces of typical anodes used in organic electronics, indium tin oxide ͑ITO͒ and poly͑3,4-ethylenedioxythiophene͒:poly͑styrenesulfonate͒ ͑PEDOT:PSS͒, with the oligomeric hole transport material N , N , NЈ, NЈ-tetrakis͑4-methoxyphenyl͒-benzidine ͑MeO-TPD͒, and studied the influence of electrical interface doping by the strong electron acceptor tetrafluoro tetracyanoquinodimethane ͑F 4 -TCNQ͒. The fundamentally di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Additionally, many photoemission studies in metal/ organic and organic/organic heterointerfaces have found interface dipoles [13][14][15][16][17][18]. The origin of interface dipoles depends on the material system.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, many photoemission studies in metal/ organic and organic/organic heterointerfaces have found interface dipoles [13][14][15][16][17][18]. The origin of interface dipoles depends on the material system.…”
Section: Discussionmentioning
confidence: 98%
“…Recently there has been considerable interest in the structural and electrical properties of ITO contact layers [4][5][6]. In this research, band structure characteristics of ITO layers are very important for analysing the contact potential of ITO electrodes and functional layers in devices [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…PEDOT:PSS is a conducting composite polymer that is widely used as anode buffer layer in OLEDs, [231][232][233][234][235][236] whose structure is shown in Figure 8. Although the improvement of the ITO anode by PEDOT:PSS has often been reported in literature, the origin of it is not well known.…”
Section: Composite Buffer Layersmentioning
confidence: 99%